2019
DOI: 10.1051/0004-6361/201935929
|View full text |Cite
|
Sign up to set email alerts
|

Broadband X-ray observations of four gamma-ray narrow-line Seyfert 1 galaxies

Abstract: Narrow-line Seyfert 1 galaxies (NLS1s) is one of the few classes of active galactic nuclei (AGN) harboring powerful relativistic jets and detected in γ rays. NLS1s are well-known X-ray sources. While in non-jetted sources the origin of this X-ray emission may be a hot corona surrounding the accretion disk, in jetted objects, especially beamed ones, the contribution of corona and relativistic jet is difficult to disentangle without a proper sampling of the hard X-ray emission. For this reason, we observed with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 126 publications
(169 reference statements)
5
6
0
Order By: Relevance
“…where r is the radius of the emitting region and τ is the observed timescale. Using the 6-hour binned γ-ray light curve derived by Gokus et al (2021), the variability between adjacent points indicated that the doubling time is ∼2−4 hours, consistent with the values observed at hard X-rays by Berton et al (2019a). If we assume that the jet structure is self-similar, and that its semiopening angle is 0.1 radians, the size of the emitting region depends on the distance of the dissipation region from the central source.…”
Section: The 2019 Flaresupporting
confidence: 74%
See 2 more Smart Citations
“…where r is the radius of the emitting region and τ is the observed timescale. Using the 6-hour binned γ-ray light curve derived by Gokus et al (2021), the variability between adjacent points indicated that the doubling time is ∼2−4 hours, consistent with the values observed at hard X-rays by Berton et al (2019a). If we assume that the jet structure is self-similar, and that its semiopening angle is 0.1 radians, the size of the emitting region depends on the distance of the dissipation region from the central source.…”
Section: The 2019 Flaresupporting
confidence: 74%
“…This result agrees with what was found by Gallo et al (2006), who derived A(V) = 1.9 ± 1.5 from the AAT spectrum 3 . As they already pointed out, this extinction is significantly higher than what can be estimated from the X-ray spectra, which instead show negligible absorption, as confirmed by more recent observations (Kreikenbohm et al 2016;Berton et al 2019a;Gokus et al 2021). They also suggested that a possible explanation for this is a very different gas-to-dust ratio than what is seen in the Milky Way, and the jet may play a role in this by transferring material from the nucleus into the NLR.…”
Section: Hα Regionsupporting
confidence: 54%
See 1 more Smart Citation
“…Other studies at infrared/optical wavelengths [18,[269][270][271][272][273][274][275][276][277][278][279] and at X-rays [254,280,281] have been done.…”
Section: Sample Study Surveysmentioning
confidence: 99%
“…This might exclude NLSy1s that are believed to be genuinely jetted, such as the ones with c-ray detections(Berton et al, 2019). Such sources are in a different accretion domain and might be more appropriately considered in the context of a scaling law with a L/L Edd dependence(Foschini, 2014).Frontiers in Astronomy and Space Sciences | www.frontiersin.org November 2021 | Volume 8 | Article 694554…”
mentioning
confidence: 99%